DIGITAL LITERACY AND ARTIFICIAL INTELLIGENCE IN TRANSFORMING LANGUAGE LEARNING IN THE INDEPENDENT LEARNING ERA - Ach. Munawi Husein; Danie Agustin; Adelia Maghfiroh (CV. ADIBA AISHA AMIRA, 2026)
This study examines the role of digital literacy and artificial intelligence in transforming language learning in the era of independent learning. It applies a qualitative library research approach by reviewing recent peer-reviewed studies published within the last five years and indexed in reputable academic databases. The literature was selected based on its relevance to digital literacy, AI literacy, language competence, learner autonomy, technology-enhanced learning, and ethical issues in education. Data were analyzed through thematic content analysis involving identification, classification, comparison, and synthesis of key findings. The results show that digital literacy is a fundamental prerequisite for the effective and responsible use of artificial intelligence in language learning. AI-supported tools, including chatbots, adaptive platforms, automated feedback systems, speech recognition, and generative applications, can improve learning flexibility, personalization, engagement, motivation, and access to continuous language practice. These technologies contribute to the development of vocabulary, grammar, writing, reading, listening, speaking, and pronunciation skills while supporting learners in planning, monitoring, and evaluating their own learning. However, the study also identifies challenges related to inaccurate information, algorithmic bias, privacy, plagiarism, overdependence, unequal access, and the declining originality of learners’ work. Therefore, artificial intelligence should be positioned as a pedagogical support tool rather than a substitute for teachers, human interaction, and critical thinking. The study concludes that the successful integration of digital literacy and AI requires clear pedagogical design, teacher guidance, ethical standards, process-based assessment, and equitable digital infrastructure. Such integration can strengthen language competence and develop autonomous, reflective, adaptive, and responsible learners in contemporary education.